Personal Selling dalam Hubungan Komunikasi Antara Barista dan Pengung Seis Caffé Medan - olyvia, tasya; Khairullah, Khairullah (Universitas Medan Area, 2025)
Communication is a fundamental aspect of human social interaction, especially in the service industry such as cafes. Personal selling is an important communication strategy in building relationships between sellers and buyers. This study aims to analyze how personal selling carried out by Seis Caffé Medan baristas contributes to building communication relationships with customers and its impact on customer loyalty. Using descriptive qualitative methods, data were collected through in-depth interviews, observations, and documentation, and then analyzed with the Miles and Huberman model. The results of the study show that the personal selling implemented by baristas at Seis Caffé Medan does not only focus on buying and selling transactions, but also on building interpersonal relationships with customers. Persuasive communication used by baristas includes friendly language, open facial expressions, and an approach that puts customers as friends, not just consumers. Adaptation in personal selling was also found to be an important factor, where new baristas need time and support from the work environment to develop their communication skills